Corporations and NGOs: When Accountability Leads to Co-optation - Baur, Dorothea (Journal of business ethics, 2012)
Interactions between corporations and nonprofits are on the rise, frequently driven by a corporate interest in establishing credentials for corporate social responsibility (CSR). In this article, we show how increasing demands for accountability directed at both businesses and NGOs can have the unintended effect of compromising the autonomy of nonprofits and fostering their co-optation. Greater scrutiny of NGO spending driven by self-appointed watchdogs of the nonprofit sector and a prevalence of strategic notions of CSR advanced by corporate actors weaken the ability of civil society actors to change the business practices of their partners in the commercial sector. To counter this trend, we argue that corporations should embrace a political notion of CSR and should actively encourage NGOs to strengthen “downward accountability” mechanisms, even if this creates more tensions in corporate–NGO partnerships. Rather than seeing NGOs as tools in a competition for a comparative advantage in the market place, corporations should actively support NGO independence and critical capacity.